The Theory of peace and war in the Holy Qur'an, verses of killing and fighting - Surat Al- Tawbah as a model - shaiban, Mohammed Abdullah (Journal of Islamic Sciences, 2019)
Allah all mighty had aimed the purpose of prophet Mohammed's message (peace be upon him), as in his words "We did not send you unless you become a merci for the whole world" and "We did not send you unless you are sent for all people to presage and portent" and from that purpose we will study the verses speak about fighting in surat Altawbah as it was the last surah came down from the Quran. Many scientists believed that this surah had drawn the final shape of the Muslim individual with others, for that reason it was important to talk about some issues the researcher sees there were some effect in understanding the texts as the transfer issue in Quran and the differences between the verb fight and kill and then study the Tawbah verses in the light of the one Quranic layout and in the light of the fighting purposes in Quran to come out with a theory to certain limitation of the human relation with each other. The researcher had come to the point that the origin of Islam is the peace and the war is only a tool to stop tyranny and to get fighters back to the right path. The Quran use of the word kill which meant to defend in most of the verses and only for those who fight to get killed.
Keywords: Peace; war; theory; fight; kill